Hubungan Antara Kebiasaan Belajar dengan Hasil Belajar PAI: Survei di SDN Kaliabang Tengah 1 Bekasi - Nur Aini; Acep Mulyadi (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2015)
This study aims to determine the relationship between study habits (X) with Islamic education learning outcomes (Y) in SDN Kaliabang Tengah 1. This study uses a quantitative survey with correlation approach. Data collection techniques used in the study using questionnaires and documents. While the results of the processing of the data obtained from study habits acquired through a questionnaire consisting of 21 items, and learning outcomes obtained through the value of one semester report cards Islamic education subjects. From the moment the product obtained calculation result of 0.485. The results showed that there was a significant positive relationship between study habits and (X) with Islamic education learning outcomes (Y) with regression Ý = a + bx or ý = 14.290+ 0.880. Thus it can be concluded that there is a significant relationship between study habits to learning outcomes Islamic education in class VI, V, VI SDN Kaliabang Tengah 1 determinant coefficient of 48%. This means showing that the study habits contribute to the learning outcomes by 48%, in addition to the learning outcomes are influenced by another factor of 52%.